Ultrathin Film Amorphous Silicon Solar Cell Performance using Rigorous Coupled Wave Analysis Method - Raghvendra Sarvjeet Dubey; Sigamani Saravanan (Center of Biomass & Renewable Energy, Diponegoro University, 2022)
The issues related to global energy needs and environmental safeties as well as health crisis are some of the major challenges faced by the human, which make us to generate new pollution-free and sustainable energy sources. For that the optical functional nanostructures can be manipulated the confined light at the nanoscale level. These characteristics are emerging and leading candidate for the solar energy conversion. The combination of photonic (dielectric) and plasmonic (metallic) nanostructures are responsible for the development of better optical performance in solar cells. Here, the enhancement of light trapping within the thin active region is the primary goal. In this work, we have studied the influence of front-ITO (rectangular) and back-Ag (triangular) nanogratings were incorporated with ultrathin film amorphous silicon (a-Si) solar cell by using rigorous coupled wave analysis (RCWA) method. The improvement of light absorption, scattering (large angle), diffraction and field distributions (TE/TM) were demonstrated by the addition of single and dual nanogratings structures. Significantly, the plasmonic (noble metal) nanogratings are located at the bottom of the cell structure as a backside reflector which is helpful for the omni-directional reflection and increased the path length (life time) of the photons due to that the collection of the charge carriers were enhanced. Further, the proposed solar cell structure has optimized and compared to a back-Ag, front-ITO and dual nanogratings based ultrathin film amorphous silicon solar cell. Finally, the obtained results were evidenced for the assistance of photonic and plasmonic modes and achieved the highest current density (Jsc) of 23.82 mA/cm2(TE) and 22.75 mA/cm2 (TM) with in 50 nm thin active layers by integration of (dual) cell structures.